Study of the effect of lead and cadmium pollution on the Soil and Wild Mushrooms Truffles (Terfezia Tirmania) From Al- Nukhib/Rutba District / Anbar Governorate / Iraq using spectroscopic analysis techniques (Journal of the College of Basic Education, 2025)
Three sampling areas of soil and Terfezia Tirmania were conducted near the mushroom, far from it, and directly around the mushroom. For each site, representative soil samples were collected in sterile tools that were prepared, especially for this purpose, then placed in sealed polyethylene bags. Flame atomic absorption spectrometry was done to analyze samples of soil and mushroom for their concentrations of some heavy metals: lead and cadmium. The analyses showed that the highest concentrations of cadmium were in the soil far from the mushroom, 5.13 ppm, while the lowest concentrations were in it, 1.44 ppm. Results of lead also showed the highest concentrations in the soil far from the fungus, 1.05 ppm, while they were lower in the fungus, 0.68 ppm. The results showed that the fungus has a low absorption capacity for cadmium, and the existence of different concentrations depending on various distances is due to various pollution sources and the capability of lead to move in the soil. Therefore, Terfezia Tirmania can be used as a good bioindicator for heavy metal soil pollution with elements such as lead and cadmium, which are of environmental concern.